2015
DOI: 10.1080/09712119.2015.1091341
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, anti-inflammatory and antioxidant activity ofNigella sativain clinically endometritic cows

Abstract: The aim of this study was to investigate the response to intrauterine infusion of Nigella sativa (NS) and ceftiofur and to evaluate the possible antimicrobial, antioxidant and anti-inflammatory effects of NS in clinically endometritic cows. A total of 30 clinically endometritic cows (10 cows in each group) were randomly divided into 3 treatment groups: an i.u. infusion of 100 mL of methanol extract of NS was given once a day during 3 days in group NS; an i.u. infusion of a 20-mL suspension (Excenel®, Pfizer) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our results demonstrated significant alterations in renal apoptotic cells, oxidative stress markers, and two important inflammatory mediators, MCP‐1 and TNF‐α, after 2 weeks of ureteral obstruction. It has been shown that NS and TQ, the most important active constituent of NS oil, have notable anti‐inflammatory and antioxidant effects in different tissues (Hosseinian et al, ; Inci et al, ; Mohebbati et al, ; Yildiz & Balikci, ) and act as potent apoptosis modulator (Li, Rajendran, & Sethi, ; Majdalawieh & Fayyad, ). Present results have shown that improvement of inflammation, oxidative stress, and apoptosis in kidneys from NS‐treated rats were accompanied by marked decrease in renal Ang II expression, which might be due to direct or indirect RAS inhibition by NS extract.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated significant alterations in renal apoptotic cells, oxidative stress markers, and two important inflammatory mediators, MCP‐1 and TNF‐α, after 2 weeks of ureteral obstruction. It has been shown that NS and TQ, the most important active constituent of NS oil, have notable anti‐inflammatory and antioxidant effects in different tissues (Hosseinian et al, ; Inci et al, ; Mohebbati et al, ; Yildiz & Balikci, ) and act as potent apoptosis modulator (Li, Rajendran, & Sethi, ; Majdalawieh & Fayyad, ). Present results have shown that improvement of inflammation, oxidative stress, and apoptosis in kidneys from NS‐treated rats were accompanied by marked decrease in renal Ang II expression, which might be due to direct or indirect RAS inhibition by NS extract.…”
Section: Discussionmentioning
confidence: 99%
“…It is established in many studies that immunosuppression which earlier required for maintaining pregnancy might be the cause of retained fetal membranes after calving thereby urging the need of immunomodulatory agents in order to maintain healthy reproductive environment of the body. Besides the immunomodulatory properties of polyherbal preparation, the antimicrobial and anti-inflammatory properties of herbs such as Nigella sativa (Yildiz and Balikci, 2016), Rubia cordifolia (Tailor et al, 2010), Tinospora cordifolia (Jeyachandran et al, 2003) provide more favorable environment and reduced pathogen invasion in reproductive tract of cows resulting in less number of cases of metritis and infections. This nutritional strategy post-partum could some extend replace the antibiotic therapy in producing animals.…”
Section: Reproductive Performancementioning
confidence: 99%
“…The present study also shows that administration of N. sativa oil significantly decreased the amount of inflammatory infiltration. A large body of experimental research has confirmed the anti-inflammatory activity of N. sativa (Ahmad et al, 2013;Yildiz and Balikci, 2016;Rahmani and Aly, 2015). This anti-inflammatory effect may be appropriate to inhibit the release of mediators by thymoquinone and other constituents of N. sativa which have anti-inflammatory,…”
Section: Effect Of Nigella Sativa Oil On Oral Mucositis In Ratsmentioning
confidence: 85%
“…One possible mechanism by which N. sativa exerts its anti-inflammatory effect is through the inhibition of both cyclooxygenase and lipoxygenase pathways (Ali and Blunden, 2003). Also, the anti-inflammatory and antioxidant effects of N. sativa oil can enhance its phagocytic activity; thus, it can play a significant therapeutic role in fighting against the microorganisms (Yildiz and Balikci, 2016). The anti-inflammatory and antioxidant effects of N. sativa oil have been found to be higher than those of thymoquinone, which is known to be the active component of N. sativa oil (Ali and Blunden, 2003).…”
Section: Effect Of Nigella Sativa Oil On Oral Mucositis In Ratsmentioning
confidence: 99%